2018
DOI: 10.21873/anticanres.12689
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine Used in Combination with Chemotherapy Synergistically Suppresses Growth and Angiogenesis In Vitro and In Vivo

Abstract: Chloroquine enhanced the anti-angiogenic effect of doxorubicin on CAM at the tested concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 36 publications
2
14
1
Order By: Relevance
“…Interestingly, anti-angiogenic treatments are frequently seen in literature involve the use of chemical substances, such as the chemotherapy drug doxorubicin [ 129 , 165 ] as well as thalidomide derivatives [ 59 ]. The application of nanoparticles such as gold [ 60 , 84 ], green [ 166 ], zinc tungstate [ 61 ] and chitosan derived nanoparticles [ 94 ] have high efficacy in the inhibition of blood vessel development, with significant reductions in blood vessel number, length and density reported.…”
Section: Cam Experimental Treatmentsmentioning
confidence: 99%
“…Interestingly, anti-angiogenic treatments are frequently seen in literature involve the use of chemical substances, such as the chemotherapy drug doxorubicin [ 129 , 165 ] as well as thalidomide derivatives [ 59 ]. The application of nanoparticles such as gold [ 60 , 84 ], green [ 166 ], zinc tungstate [ 61 ] and chitosan derived nanoparticles [ 94 ] have high efficacy in the inhibition of blood vessel development, with significant reductions in blood vessel number, length and density reported.…”
Section: Cam Experimental Treatmentsmentioning
confidence: 99%
“…This fact can favor the action of doxorubicin, since its mechanisms of action are the intercalation of DNA and inhibition of topoisomerase [38]. In addition, doxorubicin was reported to induce cytotoxicity and disrupt tube-like structures formed by human umbilical vein endothelial cells (HUVECs) as well as reduce migration, cell proliferation, and angiogenesis, according to the CAM assay [70]. Additionally, Magnelli et al described the antiangiogenic properties of alpha-bisabolol through the induction of apoptosis and inhibition of the formation of tube-like structures by HUVECs cells in vitro [71].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that autophagic responses can be triggered in vascular endothelial cells by a variety of antiangiogenic agents [28]. Although some antiangiogenic agents have been demonstrated to induce autophagic cell death in vascular endothelial cells, it is suggested that in most situations, induction of autophagy exerts cytoprotective effects on vascular endothelial cells, and this acts as an important cellular mechanism of drug resistance [28][29][30]. For instance, the antiangiogenic agent sulforaphane (SUL) induces both autophagy and apoptosis in HUVECs.…”
Section: Discussionmentioning
confidence: 99%